2020
DOI: 10.1002/jsfa.10641
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cytokine expression and upregulation of inflammatory signaling pathways in broiler chickens affected by wooden breast myopathy

Abstract: Background Wooden breast (WB) myopathy in broiler chickens is a growing challenge for the poultry industry. Previous multi‐omic data have implied that the pathogenesis of WB is associated with the activation of immune system and inflammatory response. However, the intricate mechanisms are not fully understood. This study was therefore conducted to systematically investigate the morphology, expression of cytokines as well as the underlying signaling pathways regulating the inflammatory response in pectoralis ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
4
11
0
Order By: Relevance
“…Therefore, these dysregulated cytokines could further lead to immune disorder and contribute to the aggravation of liver damage. This result also supports our recent finding of the systemic inflammatory response in WB myopathic broilers as implied by the elevation of circulating cytokines (Xing et al, 2021). Besides the secretion of cytokines, inflammatory cells can also produce excessive oxygen free radicals to attack host cells, leading to hepatocyte damage (Zhu et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, these dysregulated cytokines could further lead to immune disorder and contribute to the aggravation of liver damage. This result also supports our recent finding of the systemic inflammatory response in WB myopathic broilers as implied by the elevation of circulating cytokines (Xing et al, 2021). Besides the secretion of cytokines, inflammatory cells can also produce excessive oxygen free radicals to attack host cells, leading to hepatocyte damage (Zhu et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Greene et al (2019) demonstrated that the circulatory oxygen homeostasis was dysregulated in WB myopathic broiler chickens as indicated by the altered pressure of blood gases and hemoglobin levels. Our recent study revealed that the inflammatory cytokines including interleukin (IL)-1β, IL-8, and tumor necrosis factor (TNF)-α were enhanced in the serum of WB affected birds (Xing et al, 2021). Furthermore, lung histopathology of WB myopathic birds exhibited occasional localized multifocal lymphoplasmacytic phlebitis and more foci of chondro-osseous metaplasia compared with the unaffected birds (Lake et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary taurine could improve growth performance, pH value, and tenderness of broilers challenged with H 2 O 2 by activating NF-κB signaling [ 42 ]. These findings are in agreement with a recent work reporting that the NF-κB pathway was enhanced in wooden breasts [ 43 ], which was characterized by hardened areas, pale, and ridge-like bulges at the caudal end. Strikingly, WHC gradually decreased concomitant with the worsened wooden breast myopathy [ 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…It seems likely that broiler breast muscle myopathies are associated with inflammation [262]. The NF-κB signaling pathway was found to be induced, the mRNA expression levels of downstream inflammatory mediators were increased, and TLR levels were upregulated in Pectoralis major of Wooden breast myopathy-affected broiler chickens [263]. The authors also showed that, in the serum of broilers with breast myopathies, contents of IL-1β, IL-8, and TNF-α were increased.…”
Section: Diseasesmentioning
confidence: 94%